2021
DOI: 10.3389/fnagi.2021.738686
|View full text |Cite
|
Sign up to set email alerts
|

Relieving Cellular Energy Stress in Aging, Neurodegenerative, and Metabolic Diseases, SIRT1 as a Therapeutic and Promising Node

Abstract: The intracellular energy state will alter under the influence of physiological or pathological stimuli. In response to this change, cells usually mobilize various molecules and their mechanisms to promote the stability of the intracellular energy status. Mitochondria are the main source of ATP. Previous studies have found that the function of mitochondria is impaired in aging, neurodegenerative diseases, and metabolic diseases, and the damaged mitochondria bring lower ATP production, which further worsens the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 150 publications
(159 reference statements)
0
18
0
Order By: Relevance
“…The holdase function of prefoldin is ATP-independent, similar to stress-inducible small HSPs ( Webster et al, 2019 ). Its ATP independence raises the question of whether prefoldin has additional functions under conditions of low cellular energy levels such as mitochondrial dysfunction and metabolic disorders, aging, or chronic stress ( Chaudhari and Kipreos, 2018 ; Andreasson et al, 2019 ; Fang et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…The holdase function of prefoldin is ATP-independent, similar to stress-inducible small HSPs ( Webster et al, 2019 ). Its ATP independence raises the question of whether prefoldin has additional functions under conditions of low cellular energy levels such as mitochondrial dysfunction and metabolic disorders, aging, or chronic stress ( Chaudhari and Kipreos, 2018 ; Andreasson et al, 2019 ; Fang et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Given its pivotal role in the control of energy expenditure, it is not surprising that a dysfunctional AMPK/PGC-1α/Sirt1 signaling axis should be responsible for reduced muscle energy expenditure, as occurs in aging and in metabolic disorders, such as type 2 diabetes (T2D) [ 49 ]. Consequently, pharmacological activation of this pathway holds promise as a new strategy to protect muscle and heart function under conditions that reduce myocyte vitality (aging, hypoxia, diabetes) [ 28 , 50 , 51 , 52 , 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…Sirt1 is a member of the class III histone deacetylases with important regulatory roles in a variety of pathophysiological processes (Zeng et al, 2017). Accumulating evidence has shown that Sirt1 plays a protective role in preventing cellular metabolism, cell senescence, and inflammation by regulating several signaling pathways, especially via its ability to deacetylate target proteins (Fang et al, 2021; Xu et al, 2020). Sirt1 not only catalyzes the deacetylation of lysine residues in histone substrates such as H1, H3, and H4, but also removes many acetyl groups from nonhistone substrates (Ren et al, 2019), including peroxisome proliferator‐activated receptor‐γ coactivator‐1α, forkhead box class O family, Nrf1/2, p53, eIF2α (Prola et al, 2017), NF‐κB, and others (Maiese, 2021).…”
Section: Discussionmentioning
confidence: 99%